Hepatitis C virus infection in patients with primary biliary cirrhosis - Hsuan-Wei Chen; Hsin-Hung Huang; Ching-Huang Lai; Wei-En Chang; Yu-Lueng Shih; Wei-Kuo Chang; Tsai-Yuan Hsieh; Heng-Cheng Chu (Annals of Hepatology, 2013)
Background and aim. The aim of this study is to evaluate the role of hepatitis C virus (HCV) infection in patients with primary biliary cirrhosis (PBC).Material and methods. On the basis of a retrospective review of medical records, all patients consecutively diagnosed with PBC or HCV infection between 1999 and 2011 and who had a regular follow-up of at least 3 years were included in the study. Clinical characteristics, especially the severity of cirrhosis, were analyzed in PBC patients with HCV infection (PBC-HCV), PBC patients without HCV infection (PBC-only), and patients with only HCV infection (HCV-only).Results. A total of 76 patients with PBC, including 9 patients with HCV infection, were analyzed. Of the PBC-HCV patients, 7 (7/9, 77.8%) were women with a mean age of 55.11 ± 14.29 years. Age- and sex-matched PBC-only patients (n = 36) and HCV-only patients (n = 36) were used as control groups. In comparison to the PBC-only controls, PBC-HCV patients had a greater severity of cirrhosis based on Child-Pugh (p = 0.019) and Model for End-Stage Liver Disease (MELD) (p = 0.01) scores. However, no significant difference in the severity of cirrhosis was found between the PBC-HCV and HCV-only control patients (p = 0.94 in Child-Pugh scores; p = 0.64 in MELD scores).Conclusions. In PBC patients with concomitant HCV infection, aggressive management may be warranted in view of the associated more severe liver cirrhosis.